Executive Committee Minutes 2016-04-07 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 3/10/16 – Approved. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Revision to the Electrical Engineering curriculum approved for Senate consent calendar. CFA Report. Request for Accreditation Input. Faculty Availability for Student Advising and Office hours referred back to FSAC. Update on iPads for the Executive Committee. EPC Report. FSAC Report. Associated Students Report. Announcement that strike was postponed. Senate Agenda approved.